Creating Clinical Reasoning Assessment Tools in Different Languages: Adaptation of the Pediatric Emergency Medicine Script Concordance Test to Japanese - Nomura, Osamu; Itoh, Taichi; Mori, Takaaki; Ihara, Takateru; Tsuji, Satoshi; Inoue, Nobuaki; Carrière, Benoit (Frontiers in Medicine, 2021)
Introduction: Clinical reasoning is a crucial skill in the practice of pediatric emergency medicine and a vital element of the various competencies achieved during the clinical training of resident doctors. Pediatric emergency physicians are often required to stabilize patients and make correct diagnoses with limited clinical information, time and resources. The Pediatric Emergency Medicine Script Concordance Test (PEM-SCT) has been developed specifically for assessing physician's reasoning skills in the context of the uncertainties in pediatric emergency practice. In this study, we developed the Japanese version of the PEM-SCT (Jpem-SCT) and confirmed its validity by collecting relevant evidence. Methods: The Jpem-SCT was developed by translating the PEM-SCT into Japanese using the Translation, Review, Adjudication, Pretest, Documentation team translation model, which follows cross-cultural survey guidelines for proper translation and cross-cultural and linguistic equivalences between the English and Japanese version of the survey. First, 15 experienced pediatricians participated in the pre-test session, serving as a reference panel for modifying the test descriptions, incorporating Japanese context, and establishing the basis for the scoring process. Then, a 1-h test containing 60 questions was administered to 75 trainees from three academic institutions. Following data collection, we calculated the item-total correlations of the scores to optimize selection of the best items in the final version of the Jpem-SCT. The reliability of the finalized Jpem-SCT was calculated using Cronbach's α coefficient for ensuring generalizability of the evidence. We also conducted multiple regression analysis of the test score to collect evidence on validity of the extrapolation. Results: The final version of the test, based on item-total correlation data analysis, contained 45 questions. The participant's specialties were as follows: Transitional interns 12.0%, pediatric residents 56.0%, emergency medicine residents 25.3%, and PEM fellows 6.7%. The mean score of the final version of the Jpem-SCT was 68.6 (SD 9.8). The reliability of the optimized test (Cronbach's α) was 0.70. Multiple regression analysis showed that being a transitional intern was a negative predictor of test scores, indicating that clinical experience relates to performance on the Jpem-SCT. Conclusion: This pediatric emergency medicine Script Concordance Test was reliable and valid for assessing the development of clinical reasoning by trainee doctors during residency training.